Intracervical block compared with intramuscular sedation for dilatation and curettage - C, Poornima; Panicker, Seetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Dilatation and curettage is one of the most commonly performed office based gynecological procedures. As this procedure is associated with pain, is often done using conscious sedation. The purpose of this study is to estimate the efficacy of intracervical block (ICB) versus intramuscular (IM) sedation on pain experienced during this procedure. Methods: This was a prospective study comparing ICB with IM sedation in women undergoing dilatation and curettage (D&C) for abnormal uterine bleeding (AUB). Both groups received 400 mcg of misoprostol vaginally 1 hr before the procedure and pain was assessed during cervical dilatation, uterine wall scraping and 1 hour after the procedure by using a 10 cm visual analogue scale (VAS). Results: For the sixty women who underwent D&C there was statistically significant difference (p<0.001) in pain scale were observed between ICB and IM sedation during endometrial scraping and post procedure. Mean recovery time was 1.02 hrs in ICB group where as in IM group it was 3.78 hrs. Conclusion: Pain relief in ICB administration is more effective than IM sedation during D&C procedure. The recovery period in intracervical block is faster when compared to IM sedation. ICB is easier technique of administration, and cost effective.